Intersectionality and Indigenous Women’s Land Rights in Indonesian Agrarian Conflicts - Aprila Niravita (JUSTISIA GLOBAL EDUKASI, 2026)
Agrarian conflicts in Indonesia frequently involve competing claims over land, natural resources, and customary territories, with indigenous women often experiencing unique forms of marginalization. This article explores indigenous women’s land rights through an intersectional framework that considers the interaction of gender, ethnicity, customary identity, and socio-economic status in agrarian disputes. Using a socio-legal and qualitative research approach, the study examines legal frameworks, policy developments, and documented cases involving indigenous communities affected by land conflicts. The findings reveal that indigenous women face multiple layers of exclusion arising from both external legal structures and internal customary practices. While national laws increasingly recognize indigenous rights, implementation gaps and overlapping regulatory regimes continue to limit effective protection. Moreover, women’s participation in decision-making processes concerning land governance remains constrained by patriarchal norms embedded within both state and customary institutions. The study argues that conventional approaches to land rights often overlook the intersecting forms of discrimination experienced by indigenous women, thereby reinforcing inequalities in access, ownership, and control over land resources. Applying intersectionality theory enables a more nuanced understanding of how legal and social structures interact to shape women’s experiences in agrarian conflicts. The article contributes to contemporary debates on indigenous rights, gender justice, and legal pluralism by emphasizing the importance of inclusive land governance. It recommends integrating gender-sensitive and intersectional perspectives into agrarian policies, legal reforms, and conflict-resolution mechanisms to ensure substantive equality and sustainable protection of indigenous women’s land rights.